Impregnation of Silver Nanoparticles onto Polymers Based on Sugarcane Bagasse for the Remediation of Endocrine Disruptor–Bisphenol A from Water - Farid Mzee Mpatani; Ussi Makame Kombo; Khamis Rashid Kheir; Nahya Khamis Nassor; Daniel Joshua; Salma Saleh Mussa; Salama Abubakar Mohamed; Saide Abdulla Mbarak; Ali Shehe Hamad; Salum Ali Ahmada (Adsorption Science & Technology)
This present study introduces a contemporary innovation of synthesized polymer–silver nanoparticle nanocomposite adsorbent based on sugarcane bagasse (AgNP-SB-βCD) for the sequestration of emerging micropollutant–bisphenol A from water matrix. Batch adsorption mode was carried out to assess the effectiveness of AgNP-SB-βCD nanocomposites towards eliminating bisphenol A (BPA). Characterization techniques including SEM, FTIR, and XRD have confirmed the successful incorporation of silver nanoparticles (AgNPs) onto bagasse–polymer. At 25°C, pH 7, and contact time of 120 min, the nanocomposites had a maximum uptake capacity of 158.4 mg g-1on BPA. The equilibrium isotherm of BPA on AgNPs-SB-βCD has fitted effectively with Langmuir model while the adsorption kinetics conformed to pseudo-second order. The adsorption phenomenon was controlled mainly by physisorption (via host–guest inclusion van der Waals bonding and pore filling effect). In addition, oxidative degradation of BPA by AgNPs-SB-βCD could marginally contribute the removal of BPA due to oxidative dissolution of AgNPs at pH 7. The thermodynamic results substantiate the spontaneity and exothermic behaviors of the adsorption phenomenon. The polymeric nanocomposite adsorbent was regenerated five times (using 75% ethanol) without considerable loss of its adsorption capacity. This authenticates its reusability and consistency performances; accordingly, it can be a market competitor adsorbent for the treatment of water contaminated with BPA.